Penguatan Retorika Komunikatif Siswa Sekolah Menengah Atas untuk Meningkatkan Kemampuan Public Speaking - Dedi Gunawan Saputra; Asia M.; Ilma Rahim; Rahmi Mardatillah; Abd. Rahim (Jurnal Pengabdian Masyarakat Sains dan Teknologi, 2026)
Low courage in arguing and high communication apprehension often become major obstacles for high school students when facing academic presentations. This Community Service (PkM) program aims to strengthen students' communicative rhetoric skills and public speaking abilities at SMA Negeri 11 Makassar. Based on a needs assessment, partner students need techniques for persuasive public speaking, self-evaluation tools for their communication performance, and strategies for managing mental anxiety. The program was carried out through a practice-based reflective workshop involving 25 students from the school's intra-organizational board. Quantitative evaluation results showed a significant improvement in students' speaking competence, with the average score increasing from 58.4 (pre-test) to 86.2 (post-test). This result recorded an increase in the score difference by 27.8 points, which is equivalent to a competence growth of 47.6%, with the students' classical completeness rate reaching 92%. Qualitatively, observations and interviews confirmed changes in students' speaking behavior, which became more organized, expressive, and varied, and they were able to reduce anxiety independently. A tangible output of this activity is the Pocket Guide for Practical Public Speaking Based on Reflective Practice for partner students.